Understanding Risk Communication Through a Postcolonial Theory Perspective: Lessons from Three Studies on COVID-19 Vaccine Hesitancy - Josephine Adekola (International Journal of Disaster Risk Science)
Abstract This article uses postcolonial theory to examine optimal risk communication practices of new risks and scientific information to non-indigenous communities. The article calls on risk communication scholars and health practitioners to embrace postcolonial theory as it provides a critical and reflective framework to examine ontological beliefs and methodological and structural aspects in the communication of public health messages. The article draws on insight from three studies on COVID-19 vaccine hesitancy within Scotland’s African, Caribbean, and Black communities between March 2021 and April 2022. The article offers new insight into why some communities hesitate to respond to public health messages such as vaccine uptake advice. Therefore, risk communication scholars should use the postcolonial lens to examine their assumptions, thinking, and perspectives on communicating new science and risk information in emergencies. Postcolonial theory enables risk communication scholars to address power imbalances, representation, and inclusion challenges in public health communication and trust-building efforts.